NONLIEAR DYNAMIC BEHAVIORS ANALYSIS OF COMPLEX ROTOR-BEARING SYSTEM - LIN LuSheng; LIU GuiPing; CHEN Yuan (Jixie qiangdu)
Aiming at overcoming the deficiency of available methods for revaling the nonlinear dynamic behaviors of complex rotor-bearing system,a fluid-structure method which combined rotor dynamics with computational fluid dynamics based on dynamic mesh is proposed. This method presented in this paper first developed a rotor-bearing system,then calculated the transient oil field of journal bearing by using a dynamic mesh method for variable flow,thus calculated the shaft center trajectory for a dynamically loaded journal bearing. Finally,this method is validated with nonlinear dynamics analysis of a complex rotorbearing system. The results show that the proposed method can accurately solving the nonlinear dynamics of complex rotor-bearing system.